Dante and Augustine : linguistics, poetics, hermeneutics - Marchesi, Simone (Toronto Italian studies., 2011)
"At several junctures in his career, Dante paused to consider what it meant to be a writer. The questions he posed were both simple and wide-ranging: How does language, in particular 'poetic language, ' work? Can poetry be translated? What is the relationship between a text and its commentary? Who controls the meaning of a literary work? In Dante and Augustine, Simone Marchesi re-examines these questions in light of the influence that Augustine's reflections on similar issues exerted on Dante's sense of his task as a poet